S78 Electronic cigarette advertising impacts adversely on smoking behaviour within a London student cohort: a cross-sectional survey. (12th November 2015) - Ratneswaran, C; Judge, R; Colquhoun, M; Steier, J; Khong, TK
Abstract : Introduction: In contrast to tobacco smoking, electronic cigarette ("vaping") advertisement has been approved in the UK since January 2013. Currently, there are 2.6 million e-cigarette users in the UK. The impact of e-cigarette advertisement on tobacco use has not been studied in detail. We hypothesised that e-cigarette advertisement impacts on smoking behaviour. Methods: A structured survey was constructed to assess the impact of e-cigarette advertising on the perceived social acceptability of cigarette smoking; and, on trying both cigarettes and e-cigarettes (on a scale of 1 to 5/'not at all' to 'a great deal'). The survey was administered between January to March 2015 to London university students, before and after viewing 5 UK adverts including a TV commercial. Results: Data were collected from 106 participants (22 ± 2 years, 66%male), comprising 34 current cigarette-smokers, 57 non-smokers and 15 ex-smokers. There were 17 vapers, 82 non-vapers and 7 ex-vapers. After viewing the adverts, both smokers (2.6 ± 1.0 vs 3.8 ± 1.1, p = 0.0002) and non-smokers (3.2 ± 0.7 vs 3.7 ± 0.8, p = 0.004) felt e-cigarette advertising increased the social acceptability of smoking; and, both smokers and non-smokers were more likely to try e-cigarettes (3.6 ± 1.0 and 2.6 ± 1.0 respectively, p < 0.0001) as well as conventional cigarettes (3.4 ± 1.0 and 1.5 ± 0.9 respectively, p < 0.0001). Additionally after viewing, vapers felt e-cigarettes were 'less effective' at helping people stop smoking compared to before (3.6 ± 0. 7 vs 4.0 ± 0.6, p = 0.004). Conclusion: E-cigarette advertising encourages e-cigarette and conventional cigarette use in young smokers and non-smokers. The adverts impact on the social acceptability of smoking without regarding the importance of smoking cessation.